A cohort study on mortality among wives of workers in the asbestos cement industry in Casale Monferrato, Italy. Issue 9 (September 1993) - Magnani, C; Terracini, B; Ivaldi, C; Botta, M; Budel, P; Mancini, A; Zanetti, R
Abstract : The study investigates mortality from cancer and other diseases in a cohort of wives of asbestos cement workers in Casale Monferrato (northwest Italy). After the exclusion of women with an occupational record in the asbestos cement industry, the cohort comprised 1964 women. Their domestic exposure was estimated according to their husbands' periods of employment in the plant: 1740 had a period of domestic exposure whereas the remaining 224 married an asbestos cement worker only after he definitely stopped his activity in the asbestos cement plant; these have, therefore, been considered as unexposed. The cohort of wives was constructed entirely through official records in the town offices and is both exhaustive and unaffected by recall bias. At the end of follow up (1988) 1669 women were alive, 270 were dead and 25 (1.2%) were untraced. Main mortality analyses were only up to age 79 to reduce the misclassification of causes of death. Expected mortality was based on local rates. Mortality analyses were limited to the period 1965-88 due to the availability of local rates: in that period 210 deaths occurred among women with domestic exposure v 229.1 expected. There were four deaths from pleural tumours (one diagnosed as mesothelioma at necropsis) and six from lung cancer v. 0.5 and 4.0 expected respectively. Two further cases of mesothelioma were diagnosed by histological examination after the end of follow up. None of the three wives with histologically diagnosed mesothelioma had been engaged in industrial activities. Corresponding information for the other three cases could not be traced.